Mechanism of selenomethionine inhibiting of PDCoV replication in LLC-PK1 cells based on STAT3/miR-125b-5p-1/HK2 signaling - Ren, Zhihua; Ding, Ting; He, Hongyi; Wei, Zhanyong; Shi, Riyi; Deng, Junliang (Frontiers in Immunology, 2022)
There are no licensed therapeutics or vaccines available against porcine delta coronavirus (PDCoV) to eliminate its potential for congenital disease. In the absence of effective treatments, it has led to significant economic losses in the swine industry worldwide. Similar to the current coronavirus disease 2019 (COVID-19) pandemic, PDCoV is trans-species transmissible and there is still a large desert for scientific exploration. We have reported that selenomethionine (SeMet) has potent antiviral activity against PDCoV. Here, we systematically investigated the endogenous immune mechanism of SeMet and found that STAT3/miR-125b-5p-1/HK2 signalling is essential for the exertion of SeMet anti-PDCoV replication function. Meanwhile, HK2, a key rate-limiting enzyme of the glycolytic pathway, was able to control PDCoV replication in LLC-PK1 cells, suggesting a strategy for viruse to evade innate immunity using glucose metabolism pathways. Overall, based on the ability of selenomethionine to control PDCoV infection and transmission, we provide a molecular basis for the development of new therapeutic approaches.